2001
DOI: 10.1521/ijgp.51.4.525.51307
|View full text |Cite
|
Sign up to set email alerts
|

Patient Personality and Time-limited Group Psychotherapy for Complicated Grief

Abstract: We used a randomized clinical trial to investigate the interaction of two patient personality characteristics (quality of object relations [QOR] and psychological mindedness [PM]) with two forms of time-limited, short-term group therapy (interpretive and supportive) for 139 psychiatric outpatients with complicated grief. Findings differed depending on the outcome variable (e.g., grief symptoms, general symptoms) and the statistical criterion (e.g., statistical significance, clinical significance, magnitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 26 publications
4
123
0
7
Order By: Relevance
“…If a patient tests positive, the interviewer can acquire further information about the losses and (or) refer the patient to someone who specializes in the assessment and treatment of patients with CG. Cost-efficient treatments such as short-term group therapy can effectively treat psychiatric outpatients with CG (14,15). Before it can be treated, however, CG needs to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…If a patient tests positive, the interviewer can acquire further information about the losses and (or) refer the patient to someone who specializes in the assessment and treatment of patients with CG. Cost-efficient treatments such as short-term group therapy can effectively treat psychiatric outpatients with CG (14,15). Before it can be treated, however, CG needs to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers randomly assigned individuals to either a supportive treatment or an interpretive treatment. The researchers found that individuals with more secure attachments to the deceased (Ogrodniczuk et al, 2002) and more psychological mindedness (Piper et al, 2001) did better in both treatments. However, individuals with higher-quality relations with all attachment figures (i.e., better relational capacity) did better in the interpretive group, and individuals with lower-quality relations did better in the supportive group.…”
Section: Empirical Evidence For Bereavement Interventionsmentioning
confidence: 98%
“…Two recent studies compared the effects of two group interventions for individuals deemed to have elevated levels of grief-related symptoms 3 months following the loss of a loved one (Ogrodniczuk, Piper, McCallum, Joyce, & Rosie, 2002;Piper, McCallum, Joyce, Rosie, & Ogrodniczuk, 2001). These researchers randomly assigned individuals to either a supportive treatment or an interpretive treatment.…”
Section: Empirical Evidence For Bereavement Interventionsmentioning
confidence: 99%
“…To begin with, the effectiveness of interventions was examined with small sample sizes. Only group therapy intervention studies managed to collect the data from a large enough sample size (Piper et al 2001, Piper et al 2007.…”
Section: Group Therapymentioning
confidence: 99%
“…The benefit from the intervention may be affected by the therapists' competencies or attitudes rather than the treatment techniques. Although the changes in the outcomes were analysed according to the therapist and found no effect on the magnitude of change, there is still a doubt in drawing any definite conclusions (Piper et al 2001, Boelen et al 2007, Piper et al 2007 …”
Section: Group Therapymentioning
confidence: 99%